Draft Genome Sequences of Citrobacter freundii Strains CF04 and A41 Isolated from Moribund, Septicemic Giant Gourami (Osphronemus goramy) in Sri Lanka - Honein, Karim (Genome Announc, 2016)
Citrobacter freundii is a Gram-negative opportunistic pathogen associated with many infectious conditions including septicemia in humans and animals. Here, we announce the draft genome sequences of two multidrug-resistant C. freundii strains (CF04 and A41) isolated from septicemic giant gourami (Osphronemus goramy) collected from aquaria in Sri Lanka.